The Rise of Putonghua in Hong Kong: An Analysis of Language Use by Hongkongers and Mainland Chinese Education Migrants - Gu, Amanda (Tufts Archival Research Center, 2022)
Language use in Hong Kong is complex and ambiguous as the population comprises migrant groups globally. English enjoys a supreme status in this former British colony, and Cantonese reinforces Hong Kong's nativism. Yet, the current return to China under the “One Country, Two Systems” framework reshapes Hong Kong’s linguistic environment. Putonghua rose from a marginalized position to a critical role as a product of China’s political domination and the social interactions between Mainland and Hong Kong individuals. This thesis argues that the rise of Putonghua in Hong Kong is in part due to the influx of Chinese education migrants, raising Putonghua linguistic capital in the city. An autoethnography portrays the growing Putonghua use in present-day Hong Kong. Interview results with Chinese education migrants uncover their navigation and, specifically, their contribution to the rise of Putonghua in society.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the International Relations Program.; Advisor: Amahl Bishara.; Committee: Amahl Bishara and Elizabeth Remick.